Pengujian Getaran Massa Tidak Seimbang Menggunakan Accelerometer Adxl 335 Dengan Arduino - Perdana, Ade Wahyu; Huda, Feblil; Utomo, Sapdo (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Machines that operate under certain conditions will experience a performance degradation that will cause vibration, one of which is caused by unbalance symptoms. Machines with unbalance conditions that occur under safe conditions can damage components in a machine. One of them is the damage to the bearing and the entire shaft system of a machine. Efforts to overcome this matter required preventive maintenance with the contact measurement method by attaching a vibration sensor in the form of an ADXL335 accelerometer with the help of Arduino. Accelerometer ADXL335 is attached to the engine component that is operating with the sensor output measurement in the form of vibration signal amplitude. The unbalance indication of the test is characterized by the presence of the dominant frequency at one rotational speed (1xRPM). From the test, the result of balancing of normal condition in one rotor are 0.0165 G with balancing efficiency 78.47 %. The addition of unbalance mass on one rotor obtained balancing result that is 0.01593 G with efficiency of balancing respectively 78.09%.Keywords: vibration signal, unbalance, balancing, Accelerometer, Arduino, ADXL335, unbalance mass